Research on Pure Hydrogen Production Using a Fuel-Processing System Combined with a PSA System - Seokkyun Ko; Sangyong Lee (Applied Sciences, 2023)
Research was conducted to improve the system efficiency of a fuel-processing system combined with a hydrogen-purification system to supply hydrogen to a 10 kW residential building proton-exchange membrane fuel cell (PEMFC). The system consists of a steam-reforming reactor, a water–gas shift reactor, heat exchangers and a pressure swing adsorption (PSA) system, increasing the purity of the produced hydrogen by over 99.97%. Aspen Plus® and Aspen adsorption® simulators were used to optimize operating conditions by calculating thermal efficiency and hydrogen-production yield under various temperature and pressure conditions in the reformer. To optimize the hydrogen-production system, simulations were performed under conditions of 1 to 10 atm and 600 to 1000 °C, and simulations were also performed while maintaining the PSA pressure at 9 atm. The overall system efficiency was expressed as a function of methane conversion, and the methane conversion was expressed as a function of reformer temperature and pressure. The fuel-processing system showed the highest thermal efficiency of 82.40% at a pressure of 1 atm and a temperature range of 800 °C. For the combined system of a fuel-processing system and a hydrogen-purification system, the highest hydrogen-production yield was 43.17% at 800 °C and 1 atm.